The Effectiveness of Reality Therapy in Reducing the Potential for Relapse in Class IIA Sungguminasa Narcotics Prison Inmates - Andi Mardani; Ahmad .; Nurfitriany Fakhri (Polteknik Ilmu Pemasyarakatan, 2023)
The causes of relapse are the lack of self-control and motivation of prisoners. One of the interventions that can handle this problem is reality therapy. Reality therapy aims to teach people about skills in making decisions and convince people to be able to take responsibility for decisions that can meet their needs. Reality therapy theory centers on self-control and self-determination. The purpose of this study was to find out reality therapy is effective in reducing the potential of relapse for prisoners at the Lapas Narkotika Kelas IIA Sungguminasa. This study used a pre-experimental research design with one group pretest-posttest design. Participants in this study were 20 people. The measurement tool used is the Index of Sense of Self-control in Recovery for Drug Offenders (ISSRDO). The intervention was given in 12 sessions. Based on the results of the data analysis performed, a significance value of p=0.000 (p<0.05) was obtained. The results of the hypothesis test show that reality therapy is effective in reducing the relapse potential of prisoners who are in the high category of relapse. There is a change in the potential for relapse in prisoners before the intervention is given and after the intervention is given